2014
DOI: 10.1073/pnas.1315398111
|View full text |Cite
|
Sign up to set email alerts
|

Basal NF-κB controls IL-7 responsiveness of quiescent naïve T cells

Abstract: T cells are essential for immune defenses against pathogens, such that viability of naïve T cells before antigen encounter is critical to preserve a polyclonal repertoire and prevent immunodeficiencies. The viability of naïve T cells before antigen recognition is ensured by IL-7, which drives expression of the prosurvival factor Bcl-2. Quiescent naïve T cells have low basal activity of the transcription factor NF-κB, which was assumed to have no functional consequences. In contrast to this postulate, our data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…Miller ML et al has shown that NF-κB pathway is responsible for the transcription of the IL-7R gene in T cells [15]. Additionally, Wang H et al indicates that Notch1 pathway is associated with the expression of IL-7R in T cells and T-lymphoblastic leukemia [16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Miller ML et al has shown that NF-κB pathway is responsible for the transcription of the IL-7R gene in T cells [15]. Additionally, Wang H et al indicates that Notch1 pathway is associated with the expression of IL-7R in T cells and T-lymphoblastic leukemia [16].…”
Section: Resultsmentioning
confidence: 99%
“…Miller ML et al indicated that NF-κB pathways mediate the transcription of IL-7 receptor, thereby controlling the responsiveness of quiescent naïve T cells to IL-7 [15]. Tian B et al has shown that the tumor necrosis factor (TNF)-mediated expression of IL-7R is also dependent on NF-κB pathways in HeLa cells [25].…”
Section: Discussionmentioning
confidence: 99%
“…NF- κ B regulates inflammation, 6,7 and we recently demonstrated the biological relevance of NF- κ B in ovarian cancer. Coordinated expression of NF- κ B transcription factors and target genes were associated with poor overall survival and aggressive tumor behavior.…”
Section: Introductionmentioning
confidence: 95%
“…Stimulation with tumor necrosis factor (TNF), which is known to act through NF-kB, resulted in a slight increase in NF-kB phosphorylation across the naive CD4 + T cell population regardless of CD31 expression (S Fig 5B). Interestingly, basal NF-kB phosphorylation has been shown to play an important role in determining naïve T cell survival in rodents [48,49], prompting us to investigate this pathway further.…”
Section: Single Cell Proteomic Analysis Of Cd4 + Naïve T Cells Revealmentioning
confidence: 99%